Alternative procedure for production of correspondence (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The relations between verbal and non-verbal operant classes have been studied by an area called “say-do; do-say correspondence”. The present study verified (1) if successive manipulations of reinforcers and punishments contingent to dependent and independent operants (say/do classes), influence each other; (2) the effects of the application of reinforcers and punishment on independent operant classes and (3) if when reinforcing and punishing dependent operant classes occurs correspondence between these operant classes. In experiment I eight female university students participated, being exposed to five experimental phases. The results of experiment I showed that contingencies of reinforcement were effective to promote correspondence between independent operant classes for six of the eight participants. The two other participants did not show correspondence in all phases. In experiment II nine female university students participated, being exposed to three experimental phases. The results showed that the contingencies of reinforcement and punishment du-ring phase 2 were effective in promoting correspondence between dependent operant classes. In this experiment two variables were manipulated at the same time. To solve this problem experiment III was designed. In experiment III, eight university students participated, being exposed to three experimental phases. The results showed that the contingencies of reinforcement and punishment during phase 2 were effective in promoting correspondence between dependent operant classes. Experiment III was designed to identify which variable controlled participants’ behavior. The results showed that the controlling variable was the relation of functional dependence. Together, these experiments made possible to verify that when dependency contingencies between operant classes are organized, the probability of correspondence between say and do occurs.
Keywords: operant classes; correspondence; functional dependence-independence.